2001
DOI: 10.1099/00221287-147-12-3387
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repressor CopR: dissection of stabilizing motifs within the C terminus

Abstract: Replication of the streptococcal plasmid pIP501 is regulated by two components, CopR and the antisense RNA, RNAIII. CopR represses transcription of the essential repR mRNA about 10-to 20-fold and, additionally, prevents convergent transcription of sense and antisense RNAs. It has been demonstrated that CopR binds as a preformed dimer. DNA binding and dimerization constants were determined and amino acids were identified that are involved in DNA binding and dimerization. It was demonstrated that the Cterminal 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Their amino acid sequences diverge only at the C terminus, which is solely responsible for protein stability (Kuhn et al, 2000(Kuhn et al, , 2001. Furthermore, the three Cop operator sites are almost identical, differing only in the spacer region between binding sites I and II and in the flanking region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their amino acid sequences diverge only at the C terminus, which is solely responsible for protein stability (Kuhn et al, 2000(Kuhn et al, , 2001. Furthermore, the three Cop operator sites are almost identical, differing only in the spacer region between binding sites I and II and in the flanking region.…”
Section: Discussionmentioning
confidence: 99%
“…A 3D model of the N-terminal 63 amino acids of CopR was built, allowing the identification of amino acids involved in DNA binding and dimerization (Steinmetzer et al, 2000a(Steinmetzer et al, , b, 2002a. Furthermore, it was established that the structured acidic C terminus of CopR that forms a b-strand is necessary for stabilization of the protein (Kuhn et al, 2000(Kuhn et al, , 2001. A fluorescence energy study revealed that CopR bends the operator DNA slightly -20-25 u -upon binding (Steinmetzer et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…CD measurements revealed that the C-terminus of CopR that contains alternating hydrophilic and hydrophobic aa residues is structured and forms a β-strand (Kuhn et al, 2000 ). Further analysis of the stabilizing motifs within the C-terminus (Kuhn et al, 2001 ) showed that both the wild-type (QVTLELEME, Figure 3A ) and an artificial (QVTVTVTVT) β-strand structure (variant CopRVT) between aa 76 and 84 stabilized the corresponding protein derivatives. By contrast, replacement of the β-strand by an α-helix or an unstructured sequence significantly or moderately destabilized the protein.…”
Section: Pip501 Replication and Copy Number Controlmentioning
confidence: 99%
“…Eight amino acids are involved in forming the dimeric interface, and two of them required for correct folding of the monomer (41,42). The structured acidic C terminus of CopR is important for protein stability and contains a stretch of alternating hydrophilic and hydrophobic amino acids that form a β-strand (43,44). Its deletion does not impair the in vivo function of CopR, but decreases CopR half-life from 42 min to 4 to 5 min (43).…”
Section: Introductionmentioning
confidence: 99%